Nana's hog - Brimner, Larry Dane.; Miller, Susan, 1956- (New York : Children's Press, 1998)
Although people think her behavior improper, Nana rides a hog through town.
1.7
K-3
Keywords: Grandmothers -- Fiction; Pigs -- Fiction; Individuality -- Fiction; Stories in rhyme; Grandmothers -- Fiction; Pigs -- Fiction; Individuality -- Fiction; Stories in rhyme